2D - QSar studies on escherichia coli Acrab-Tolc efflux pump inhibitors : The student scientific research final report year 2019 / Nguyen Vu Thuy Vy author of research; Phan Thien Vy instructor - Nguyen, Vu Thuy Vyauthor of research
Code of research: D.2019.4